Phytochemicals, antioxidant, and antityrosinase activities of Achillea sivasica Çelik and Akpulat. (18th December 2017) - Haliloglu, Yesim; Ozek, Temel; Tekin, Mehmet; Goger, Fatih; Baser, Kemal Husnu Can; Ozek, Gulmira
ABSTRACT: The present study is the first report on essential oil (EO) composition, phytochemicals, and biological potential of Achillea sivasica tested against free radicals, oxidative damage, and tyrosinase enzyme. Gas-Chromatography Flame Ionization Detector (GC-FID) and gas chromatography/mass spectrometry (GC/MS) analyses revealed that β-pinene (11.5%, 9.3%, and 6.7%), β-pinene (7.0%, 3.0%, and 6.9%), 1, 8-cineole (18.0%, 22.1%, and 6.7%), and camphor (7.6%, 4.1%, and 9.0%) were the major constituents in the EOs from the herb, flower, and leaves, respectively. Liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) analysis of the extracts revealed the presence of caffeoylquinic acid derivatives, luteolin, apigenin, patuletin, isorhamnetin, cirsimaritin, and santin. The leaf extracts demonstrated strongest free radical scavenging, cupric reducing, lipid peroxidation inhibition, and antityrosinase activities.